Impact of Ultrasonography-Guided Transversus Abdominis Plane Block and Local Anesthetic Infiltration in the Surgical Field on Postoperative Analgesic Requirements for Laparoscopic Cholecystectomy Procedures - Mustafa Kahveci; Fatma Yeşim Çokay Abut; Gökhan Erdem (İstanbul Medical Journal)
Introduction: This study aimed to assess the impact of intraperitoneal local anesthetic infiltration and ultrasonography-guided transversus abdominis plane (TAP) block on postoperative pain intensity and opioid usage within the first 24 hours after laparoscopic cholecystectomy. Methods: Sixty patients classified under the American Society of Anesthesiologists 1-2-3 risk groups participated in this prospective, controlled, and randomized study and were divided. into three groups. The TAP group (n=20) underwent bilateral TAP blocks with 20 mL of 0.25% bupivacaine. prior to surgical incision. The following gallbladder removal by the surgical team, the intraperitoneal group (n=20) received 10 mL of 0.5% bupivacaine infiltration into the bladder bed. The control group (n=20) did not receive local anesthesia via TAP block or intraperitoneally. Postoperative pain scores on the Numeric Rating Scale [(NRS) 0-10] were recorded at 1, 2, 4, 8, and 24 hours. Additionally, the total tramadol dosage (mg) consumed at the 24th postoperative hour and the frequency of additional analgesic use were documented in the case report form. Results: The postoperative NRS scores of both the TAP block and intraperitoneal groups were significantly lower than those of the control group (p<0.05). Moreover, there was no notable difference between the TAP block and intraperitoneal groups concerning NRS scores (p>0.05). Similarly, no significant variance was observed in the total tramadol dosage among the TAP block, intraperitoneal, and control groups (p>0.05). Conclusion: The analgesic efficiencies of TAP block and intraperitoneal local anesthesia infiltration were similar, and both groups provided more effective analgesia than the control group.